HEGEMONIC MASCULINITY IN OKKY MADASARI’S BOUND - Fikri Arik Yassar (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
The hegemonic notions of masculinity causes negative effects in women's struggle throughout history, while its ideal of being a man also sets nearly impossible standards for even men to achieve which could physically and mentally bring negative impacts for men. Okky Madarasi's Bound explores various issues entangled with social injustice through the characters' journey as lower-class and marginalized individuals. This study analyzed the hegemonic masculinity and its systemic practice as the root of social injustice depicted in the novel. The method used is by applying the concept of hegemonic masculinity theory by R. W. Connell which is a branch of gender studies, and masculinity in trans-body for additional approach on one of main characters. This study also used the dynamic of gender inequality based on Scott-Samuel's concept, and Johan Galtung’s structural violence in which to analyze the hegemonic masculinity structural cycle into the main data to underline the cycle and dimension of its practice. The result found the dominant characters utilized the abuse of power against the subordinate individuals for personal gains through various types of structural violence. Distinctively, lower-class women and men are affected by the practice of hegemonic masculinity in interpersonal, institutional, and structural dimensions. Keywords: hegemonic masculinity, structural violence, the abuse of power, social injustice